2002
DOI: 10.1208/ps040317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the formulation requirements of dosator and dosing disc automatic capsule filling machines

Abstract: The overall objective of this study was to provide 'semi-quantitative' or 'rigorous' definitions of the fluidity, lubricity and compactibility requirements of formulation for representative dosator and dosing disc capsule filling machines. To that end, model formulations were developed for those properties using Carr's compressibility index, ejection force, and plug breaking force at a specified compression force to gauge fluidity, lubricity, and compactibility, respectively. These formulations were each encap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2003
2003
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…7 The "net work done" method using a texture analyzer (with a load cell of 50 kg, equivalent of 500 N) was employed to simulate the lubrication efficacy of MS for use in a tamping capsule-filling machine, where forces in the range of 100 to 200 N are involved. 8 The study had identified the best and the worst performers and related their performance to solidstate properties. Tableting, which requires application of much higher forces (in the range of 5-15 kN), can be divided into 2 distinct stages: initial compression (reduction in bulk volume because of displacement of gaseous phase) and consolidation (increase in mechanical strength because of cold welding and fusion bonding between the particles).…”
Section: Introductionmentioning
confidence: 99%
“…7 The "net work done" method using a texture analyzer (with a load cell of 50 kg, equivalent of 500 N) was employed to simulate the lubrication efficacy of MS for use in a tamping capsule-filling machine, where forces in the range of 100 to 200 N are involved. 8 The study had identified the best and the worst performers and related their performance to solidstate properties. Tableting, which requires application of much higher forces (in the range of 5-15 kN), can be divided into 2 distinct stages: initial compression (reduction in bulk volume because of displacement of gaseous phase) and consolidation (increase in mechanical strength because of cold welding and fusion bonding between the particles).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an optimum range of powder flow exists, above and below which fill weight uniformity will be poor. Heda et al (2002) suggested a Carr's index in the range 20±30%, whereas suggested a range of 15±30%.…”
Section: Fill Weight Uniformitymentioning
confidence: 98%
“…However, fill weight uniformity can also be poor for free-flowing powders, as a result of powder flooding, leading to inconsistent filling of the dosing disk. In addition, powders with excellent flow properties may be difficult to compress, leading to weak plugs that Powder formulation design for tamp filling processes break on ejection (Heda et al 2002). Therefore, an optimum range of powder flow exists, above and below which fill weight uniformity will be poor.…”
Section: Fill Weight Uniformitymentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16] Yet others suggested the need for an optimum flow property as a requirement for low capsule weight variation. 13,17 The flow of powders is influenced by various factors including interparticle forces, surface irregularities, moisture, particle size, density, and particle shape. The use of any single flow test cannot account for all these factors 18 and a combination of flow tests is recommended.…”
Section: Powder Characteristics and Capsule Fillingmentioning
confidence: 99%